Early 68GA-PSMA PET/MRI acquisition: assessment of lesion detectability and PET metrics in patients with prostate cancer undergoing same-day late PET/CT. Issue 11 (November 2017) - Domachevsky, L.; Bernstine, H.; Goldberg, N.; Nidam, M.; Stern, D.; Sosna, J.; Groshar, D.
Abstract : Aim: To compare lesion detectability and positron-emission tomography (PET) metric measurements between early-PET/magnetic resonance imaging (MRI) acquisition and same-day PET/computed tomography (CT). Materials and methods: The study was approved by the institutional review board and written informed consent was obtained from all patients. Twenty-one patients underwent non-time-of-flight (TOF) PET/MRI immediately following 68 GA-prostate-specific membrane antigen (PSMA) tracer injection in two steps: firstly, early prostate PET/MRI (pPET/MRI) and early whole-body (WB) PET/MRI (wbPET/MR) followed by WB TOF PET/CT (wbPET/CT). Lesion detectability was compared between wbPET/MRI and wbPET/CT while PET metric measurements were compared between pPET/MR, wbPET/MRI, and wbPET/CT. Results: Sixty-one and 63 lesions were found on wbPET/MRI and wbPET/CT, respectively (K=0.95, 95% confidence interval (CI)=0.89–1.0) with very good correlation between PET metric measurements ( r= 0.91; p= 0.001). Bland–Altman plots demonstrated a mean percentage difference between wbPET/CT with wbPET/MRI of 34.4% with 95% limits of agreement (LOA) between –39% to 107.9% for metabolic tumour volume (MTV) and a mean difference of 30% with LOA between –13.4% to 73.4% for peak standardised uptake value (SUVpeak). Conclusion: Early PET/MRI demonstrates very good lesion detectability agreement and correlation with PET metrics compared to same-day PET/CT. Nevertheless, LOA are far beyond the clinically acceptable range, and therefore, PET/CT and early PET/MRI metrics cannot be used interchangeably. Highlights: Early-PET/MR demonstrates very good lesion detectability agreement compared to same-day PET/CT. Early-PET/MR demonstrates PET metrics correlation compared to same-day PET/CT. Early PET/MR and PET/CT metrics cannot be used interchangeably despite good metrics correlation.